Ethnicity and the Persistence of Inequality - Thorp, R. author. aut Link
XIV, 238 p.
Keywords: Understanding why inequality is so great and has persevered for centuries in a number of Latin American countries requires tools that go beyond economics. Investigating the case of Peru, this book explores how inequality is embedded in institutions that constitute the interface between the economy, the polity and geography of the country.